Complex influence of the phases of the life cycle of construction projects on the effectiveness of managing innovative strategies of participants in the construction market - Popovychenko, I.; Grabchak, D.; Kryvushchenko, S.; Herasymchuk, Y.; Ovsyanik, M. (Ways to Improve Construction Efficiency, 2024)
The complex impact of the life cycle phase of construction projects on the effectiveness of managing innovation strategies of construction market entities is an aspect of modern management. The life cycle of a construction project includes such stages as initiation, design, construction, operation and disposal, each of which has a special impact on strategic decision-making. Management of innovation strategies within these stages involves the application of forecasting methods, adaptation to changing conditions, optimization of resources and increasing investment efficiency. At the initiation stage of the formation of the project concept, its technical and economic parameters are entered, risks and opportunities for integrating the latest technologies are assessed. The level of innovation at this stage determines the competitiveness of the project and its compliance with modern trends in sustainable construction. Design includes the development of technical documentation, the selection of constructive solutions and materials, which contributes to the implementation of energy-efficient technologies, digital models of management and automation of construction processes. Construction is a key stage in the implementation of innovative strategies, starting with the introduction of technological solutions, the use of modern methods of work organization and resource management. At this stage, the importance of digital technologies is increasing, including BIM modeling, robotization and the use of artificial intelligence. Operation of a construction site ensures the effective use of engineering systems, the use of smart management technologies and monitoring of energy consumption. Innovative approaches at this stage contribute to reducing operating costs, increasing environmental friendliness and improving user comfort. The final stage of the life cycle is associated with the dismantling or reconstruction of a construction site. The use of circular approaches, reuse of materials and ecological recycling technologies helps reduce the negative impact on the environment and increases the efficiency of resource management. The synergy of innovative strategies at all stages of the project life cycle allows for the comprehensive development of construction market entities.